2022
DOI: 10.1038/s41598-022-18458-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing preoperative risk of STR in skull meningiomas using MR radiomics and machine learning

Abstract: Our aim is to predict possible gross total and subtotal resections of skull meningiomas from pre-treatment T1 post contrast MR-images using radiomics and machine learning in a representative patient cohort. We analyse the accuracy of our model predictions depending on the tumor location within the skull and the postoperative tumor volume. In this retrospective, IRB-approved study, image segmentation of the contrast enhancing parts of the tumor was semi-automatically performed using the 3D Slicer open-source so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…(3) Irregularly shaped MSWMs are significantly more challenging to operate and are at an increased risk of subtotal resection compared with regularly shaped MSWMS. This finding has been described by Musigmann et al [ 43 ], who performed a retrospective review using radiomics and machine learning to assess the preoperative risk of subtotal resection in skull meningiomas. Skull-base meningiomas or posterior fossa meningiomas with an irregular shape are at an increased risk of incomplete resection.…”
Section: Discussionsupporting
confidence: 60%
“…(3) Irregularly shaped MSWMs are significantly more challenging to operate and are at an increased risk of subtotal resection compared with regularly shaped MSWMS. This finding has been described by Musigmann et al [ 43 ], who performed a retrospective review using radiomics and machine learning to assess the preoperative risk of subtotal resection in skull meningiomas. Skull-base meningiomas or posterior fossa meningiomas with an irregular shape are at an increased risk of incomplete resection.…”
Section: Discussionsupporting
confidence: 60%
“…Krähling et al developed an MRI-based radiomics model to predict mitotic cycles in intracranial meningiomas before surgery [3]. In Musigmann et al, it was shown that ML algorithms can predict possible total and subtotal resections of skull meningiomas using pre-treatment T1 post-contrast MR images [4].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning meningiomas, a few previous studies have explored the utility of radiomics for the prediction of recurrence in surgically treated meningiomas 14 . Previous studies have already shown that statements regarding the probability of complete surgical resectability of meningiomas can be made by radiomics-based analysis of MRI images 15 . Furthermore, there are research approaches that evaluate semantic features such as heterogeneity of the tumour tissue, external shape or the mass effect caused by the tumour using radiomics-based analysis for meningioma grading 16 .…”
Section: Introductionmentioning
confidence: 99%